Twistor and polytope interpretations for subleading color one-loop amplitudes - Nastase, Horatiu [UNESP]; Schnitzer, Howard J. (Elsevier B.V., 2012)
We use the relation of the one-loop subleading-color amplitudes to the one-loop n-point leading color amplitudes in N = 4 SYM, to derive a polytope interpretation for the former in the MHV case, and a representation in momentum twistor space for the general N(k) MHV case. These techniques are explored in detail for the 5-point and 6-point amplitudes. We briefly discuss the implications for IR divergences. (C) 2011 Elsevier B.V. All rights reserved.